Biomechanics and motor control : defining central concepts - Latash, Mark L., 1953-; Zatsiorsky, Vladimir M., 1932- (London, UK ; San Diego, CA, USA : Academic Press is an imprint of Elsevier, 2016)
Biomechanics and Motor Control: Defining Central Concepts' provides a thorough update to the rapidly evolving fields of biomechanics of human motion and motor control with research published in biology, psychology, physics, medicine, physical therapy, robotics, and engineering consistently breaking new ground. This book clarifies the meaning of the most frequently used terms, and consists of four parts, with part one covering biomechanical concepts, including joint torques, stiffness and stiffness-like measures, viscosity, damping and impedance, and mechanical work and energy. Other sections deal with neurophysiological concepts used in motor control, such as muscle tone, reflex, pre-programmed reactions, efferent copy, and central pattern generator, and central motor control concepts, including redundancy and abundance, synergy, equilibrium-point hypothesis, and motor program, and posture and prehension from the field of motor behavior. The book is organized to cover smaller concepts within the context of larger concepts. For example, internal models are covered in the chapter on motor programs.
Part 1. Biomechanical concepts. Joint torque -- Stiffness and stiffness-like measures -- Velocity-dependent resistance -- Mechanical work and energy -- Part 2. Neurophysiological concepts. Muscle tone -- Reflexes -- Preprogrammed reactions -- Efferent copy -- Central pattern generator -- Part 3. Motor control concepts. Redundancy and abundance -- Motor synergy -- Equilibrium-point hypothesis -- Motor program -- Part 4. Examples of motor behaviors. Posture -- Grasping.
Includes bibliographical references and index.
Print version record.
Keywords: Motor ability; Human mechanics; Human mechanics; Motor ability; x; 2; 2; Motor Activity -- physiology; Movement -- physiology; Electronic books; Electronic book